2014
DOI: 10.1002/ps.3723
|View full text |Cite
|
Sign up to set email alerts
|

Activity of flonicamid on the sweet potato whitely Bemisia tabaci (Homoptera: Aleyrodidae) and its natural enemies

Abstract: Flonicamid is an effective tool for the management of B. tabaci populations from Crete, and initial studies indicate that it could be combined with B. tabaci natural enemies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 34 publications
5
38
0
Order By: Relevance
“…Recently, an increasing number of new insecticides have been developed and applied in IPM programs for the control of whitefly, and they are expected to be safe for biocontrol agents of these pests . However, E. formosa often exhibits greater susceptibility to insecticides than its hosts .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, an increasing number of new insecticides have been developed and applied in IPM programs for the control of whitefly, and they are expected to be safe for biocontrol agents of these pests . However, E. formosa often exhibits greater susceptibility to insecticides than its hosts .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an increasing number of new insecticides have been developed and applied in IPM programs for the control of whitefly, and they are expected to be safe for biocontrol agents of these pests. 20,[45][46][47] However, E. formosa often exhibits greater susceptibility to insecticides than its hosts. 44,48 In our study, significant differences were found among the toxicities of eight insecticides at their recommended field concentrations to E. formosa adults under laboratory conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Flonicamid is a novel systemic insecticide that belongs to pyridinecarboxamide group and acts as irreversible inhibitor of aphid feeding (Roditakis et al, 2014). This compound was discovered by Ishihara Sangyo Kaisha, Ltd., Japan and launched in many parts of the world such as USA, Brazil, France and Korea Since 2005 (Morita et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Flonicamid, a pyridine carboxamide, is a novel insecticide that is in the selective Hemiptera‐feeding blocker group (mode of action group 9C; classification by IRAC, http://irac-online.org). The insecticidal mechanism appears to be starvation caused by irreversible inhibition of feeding activity . Flonicamid inhibits the feeding activity of insects immediately after treatment and is an effective insecticide against sap‐sucking insects such as whiteflies, aphids, leafhoppers (jassids), thrips, scales and mealybugs .…”
Section: Introductionmentioning
confidence: 99%
“…The insecticidal mechanism appears to be starvation caused by irreversible inhibition of feeding activity. 10 Flonicamid inhibits the feeding activity of insects immediately after treatment and is an effective insecticide against sap-sucking insects such as whiteflies, aphids, leafhoppers (jassids), thrips, scales and mealybugs. 11 Flonicamid inhibited the feeding activity of aphids within 0.5 h of treatment, without showing symptoms of neuronal intoxication, and feeding activity was inhibited until death.…”
Section: Introductionmentioning
confidence: 99%